(untitled) (Proceedings of International Educators Conference, 2023)
The amount of value added tax in our country is increasing year by year. Budget revenues from value added tax on domestic products increased one and a half times over three years - from 20.5 trillion soums (2.1 billion) in 2020 to 32.8 trillion soums (3.0 billion) in 2022. Value added tax on imports has almost doubled during this period - from 19.7 trillion soums to 38.7 trillion soums. Last year, VAT revenues provided one third of the state budget revenues. 71.5 trillion soums of VAT collected in 2022 significantly exceeded the target of 53.3 trillion soums. In 2023, the value added tax revenues in the amount of 63.8 trillion soums are expected in the budget of Uzbekistan. The number of VAT payers increased by 14.4% in 2022 alone and reached 171.9 thousand in December1